Study of population dynamics silver rasbora (Rasbora argyrotaenia Bleeker, 1849) in PB Soedirman Reservoir, Banjarnegara - Anggararatri, Yasinta; Muslih; Rukayah, Siti; Lestari, W. (Genbinesia Journal of Biology, 2023)
Silver rasbora (Rasbora argyrotaenia Bleeker, 1849) is one of the native species found in Panglima Besar (PB.) Soedirman Reservoir. High economic value of silver rasbora causes fishermen to tend overfishing. This over-exploitation threatens the native species of fish. Therefore, this study aims to determine several parameters of fish population dynamics so that they become the basis for fisheries management. Sampling was carried out at the PB. Soedirman Reservoir in November 2021, January 2022, and March 2022 using a survey method. The result of this research is, the population of silver rasbora was 3097 individuals dominated by male and small-size fish 0.5-8.5 cm. Length and weight relationship obtained b value <3 which means it is negative allometric. The condition factor ranged from 1.005 to 1.068. Total mortality value (Z) 6.21 per year, natural mortality (M) 1.69 per year, fishing mortality (F) 4.52 per year, with exploitation rate (E) 0.73 per year. The total length of silver rasbora fish obtained ranged from 0.5 to 8.5 cm. The maximum length (L∞) = 12.93 cm and K = 0.62 per year with the Von Bertalanffy growth equation, Lt = 12.93 (1-e(-0.62(t-0.3291))). The yield value per recruit analysis showed that the optimum exploitation was 0.224 and the current exploitation rate was 0.73. The population of silver rasbora was over-exploitation, especially in small-size fish.